COMPOSITIONAL FEATURES OF TERCET IN WORLD LITERATURE - SA Khodjaev (Scholar Express Journal, 2022)
The article discusses the role and importance of the principle of the tercet in the creation of fiction. It is shown that the trilogy has subtle, cohesive, etc., depending on the nature of the event chosen for the work. Sources of world literature have been used to prove the opinion. Works in foreign languages have been translated from the original
Keywords: Composition; Architectonics; Image; Tercet